2013
DOI: 10.1128/aem.02602-12
|View full text |Cite
|
Sign up to set email alerts
|

New Biotransformation Process for Production of the Fragrant Compound γ-Dodecalactone from 10-Hydroxystearate by Permeabilized Waltomyces lipofer Cells

Abstract: A new biotransformation process for the production of the flavor lactone was developed by using permeabilized Waltomyces lipofer, which was selected as an efficient ␥-dodecalactone-producing yeast among 10 oleaginous yeast strains. The optimal reaction conditions for ␥-dodecalactone production by permeabilized W. lipofer cells were pH 6.5, 35°C, 200 rpm, 0.7 M Tris, 60 g/liter of 10-hydroxystearic acid, and 30 g/liter of cells. Under these conditions, nonpermeabilized cells produced 12 g/liter of ␥-dodecalacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 35 publications
2
34
1
Order By: Relevance
“…Braga et al investigated the influence of different castor oil concentrations (10 g·L ‐1 , 30 g·L ‐1 and 50 g L ‐1 ) on γ‐decalactone production in flask experiments, and concluded that the best substrate concentration was 30 g·L ‐1 of castor oil, obtaining an aroma production of 1.8 g·L ‐1 . An et al also studied the influence of different substrate concentrations on the production of γ‐dodecalactone by permeabilized Waltomyces lipofer cells. They observed that increasing the substrate concentration resulted in proportional increases in the production of γ‐dodecalactone.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Braga et al investigated the influence of different castor oil concentrations (10 g·L ‐1 , 30 g·L ‐1 and 50 g L ‐1 ) on γ‐decalactone production in flask experiments, and concluded that the best substrate concentration was 30 g·L ‐1 of castor oil, obtaining an aroma production of 1.8 g·L ‐1 . An et al also studied the influence of different substrate concentrations on the production of γ‐dodecalactone by permeabilized Waltomyces lipofer cells. They observed that increasing the substrate concentration resulted in proportional increases in the production of γ‐dodecalactone.…”
Section: Resultscontrasting
confidence: 99%
“…In experiments with 30 g·L ‐1 of castor oil, a 2‐fold increase in cell concentration leads to a 2.2‐fold enhancement in lactone production (1.2 ± 0.1 g·L ‐1 and 2.7 ± 0.4 g·L ‐1 , for 30 g·L ‐1 and 60 g·L ‐1 cell concentration, respectively). An et al conducted experiments varying cellular concentrations (0–50 g·L ‐1 ) and analyzed its impact on γ‐decalactone production by permeabilized Waltomyces lipofer cells. They observed that at concentrations less than 30 g·L ‐1 of permeabilized cells, γ‐dodecalactone production increased as the concentration of permeabilized cells increased; however, at concentrations higher than 30 g·L ‐1 γ‐dodecalactone production reached a plateau, determining the optimal cell concentration at 30 g·L ‐1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two mutant strains produced higher aroma concentration for 30 g L −1 CO than the WT. The influence of different substrate concentrations on ␥-dodecalactone production by permeabilized Waltomyces lipofer cells was also studied by An et al [35]. They observed a proportional increase in the production of ␥-dodecalactone with a substrate concentration increase.…”
Section: Batch Culturesmentioning
confidence: 91%
“…Solvents (acetone, ethanol, methanol, and toluene), detergents (Tween 20, Tween 80, and Triton X-100), salts (NaCl and MgCl 2 ), and other chemicals (EDTA) have been used to permeabilize cells [11,13,[18][19][20]. To increase 13-HODE production, recombinant cells were permeabilized by treatment with solvents, including acetone, dimethyl sulfoxide (DMSO), ethanol, methanol, and 2-propanol (Supplementary data, Fig.…”
Section: Permeabilization Of Recombinant Cells For Increased Productimentioning
confidence: 99%